America : Americanische Staaten. - Kiepert, Heinrich, 1818-1899 (Geographisches Institut, 1857)
Map shows major cities, political divisions, areas of Native American habitation; [modern day] Alaska and the Bering Strait are overprinted "Russisches Reich"; [modern day] Canada overprinted with "Britisches Nord America"; western United States includes Washington, Oregon, Nebraska, Kansas, Utah, New Mexico, "Minisotah," and "Indian" territories. Includes color key to European possessions, translated key to abbreviations, list of major mountain peaks, and letter keys to Mexican states and New England states. Relief shown by hachures. Scale not given.